RELATIONSHIP OF FEMALE AGE AND SPERM QUALITY WITH THE SUCCESSFUL OF IUI LITERATURE REVIEW - Dhea Hesty Purwaningrum; Sri Ratna Dwiningsih; Sulistiawati Sulistiawati (UNIVERSITAS AIRLANGGA, 2021)
AbstractBackground: Infertility in developing countries is higher at 30% compared to developed countries at 5-8%. The factors that influence infertility are maternal (women) age and sperm factors. Therapy in handling infertility in the form of Assisted Reproductive Technology (ART) with one of them is Intrauterine Insemination (IUI). The success rate of IUI is the percentage of IUI programs that give results as desired depending on the type of calculation used such as pregnancy rate or live birth rate. Method: This research is a literature review. The research question with PICO standard is